Tutoring Adolescents in Literacy: A meta-analysis - Jun, Seung; Ramirez, Gloria; Cumming, Alister (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2010)
What does research reveal about tutoring adolescents in literacy? We conducted a meta-analysis, identifying 152 published studies, of which 12 met rigorous inclusion criteria. We analyzed the 12 studies for the effects of tutoring according to the type, focus, and amount of tutoring; the number, age, and language background of students; and the quality of the research. Despite variability, these studies suggest benefits, notably for cross-age tutoring, reading, and small tutoring programs of lengthy duration.